2022
DOI: 10.1371/journal.pone.0270972
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of experimental autoimmune uveitis by intravitreal AAV-Equine-IL10 gene therapy

Abstract: Equine recurrent uveitis (ERU) is a spontaneous, painful, and vision threatening disease affecting up to 25% of equine populations worldwide. Current treatments of ERU are non-specific and have many side effects which limits them to short-term use. In order to develop an effective therapy for ERU, we investigated the use of adeno-associated virus (AAV) gene therapy, exploiting a natural immune tolerance mechanism induced by equine interleukin-10 (Equine-IL10). The purpose of this study was to evaluate the ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…Recently, AAV-equine (eq)IL-10 was demonstrated to be safe and effective in inhibiting uveitis in a well-established model of NIU-the experimental autoimmune uveitis (EAU) rat model. 49,50 In these experiments, it was shown that both low and high doses of AAV-eqIL-10 suppressed the development of ocular inflammation significantly in rats with EAU. In addition, AAV-eqIL-10 treatment led to the reduction of aqueous humor inflammatory cell counts and histopathologic scores.…”
Section: Uveitismentioning
confidence: 88%
See 2 more Smart Citations
“…Recently, AAV-equine (eq)IL-10 was demonstrated to be safe and effective in inhibiting uveitis in a well-established model of NIU-the experimental autoimmune uveitis (EAU) rat model. 49,50 In these experiments, it was shown that both low and high doses of AAV-eqIL-10 suppressed the development of ocular inflammation significantly in rats with EAU. In addition, AAV-eqIL-10 treatment led to the reduction of aqueous humor inflammatory cell counts and histopathologic scores.…”
Section: Uveitismentioning
confidence: 88%
“…[6][7][8][9] Gene transfer of therapeutic proteins to treat naturally occurring ocular diseases is becoming more feasible based on the results of research studies in models of uveitis and other ocular diseases. 41,50,54,55 These efficacy and safety studies are paving the way for clinical trials in animals with naturally occurring immune-mediated diseases, such as a therapeutic clinical trial for AAV-eqIL-10 in horses with ERU. This AAV-IL-10 clinical trial will be the first trial of AAV gene therapy for the treatment of uveitis in any species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of naturally occurring uveitis. 48,49 These studies are reviewed in more detail in the companion Currents in One Health by Gilger, AJVR, December 2022.…”
Section: Uveitismentioning
confidence: 99%
“…Immunosuppressive gene therapies are in the preclinical evaluation stages and, if determined safe, may be effective therapies for uveitis in both horses and humans. 48 If approved by the USDA, a clinical trial in horses of the use of an AAV delivering equine IL-10 will be the first of its kind in any animal for the long-term treatment in the evaluation and prevention of posterior capsular opacity (PCO), a condition that results in development of opacity in the eye and decreased vision from lens epithelial regrowth and/or posterior lens capsule fibrosis after cataract surgery. 64 Dogs develop a rapid and severe PCO after canine cataract surgery.…”
Section: Cataractsmentioning
confidence: 99%